Sixty and the concept of the failed state (Journal of Human Sciences, 2020)
The failed state is the state that is based on a weak system that is unable to control and apply the foundations of governance to all parts of the state. It is the state that has a weakness in the exploitation of the resources available to it, including natural, human and material resources. This weakness lds  its failure in all areas of life, and provides an opportunity For other countries, especially those economically and militarily able to control them to plunder their goods and resources, and control their internal and external affairs using flawed arguments, knowing that declaring the failure of a country needs to address several aspects to assess its position and then make a judgment about it, and it is done To report it officially, many especially at the political level and the consequences accompanied.  A failed state is a country with a weak or ineffective central government that has little control over much of its territory. The level of control needed is weak. Or it is the one that cannot control all of its territory and is forced to seek foreign aid and assistance so that many donor countries that provide support in its forms and types impose their conditions for assistance, "according to Chomsky.it is the country which does not want to protect its people and “considers itself above the law, whether domestic or international.” The failure of the state is theoretically defined as the inability of the state to perform its functions that no other party can perform. That is, it is unable to produce the factors of its continuation within the framework of its recognized geographical borders. The failure of states often comes in parallel levels, neither of which can be held which is the result, so that failure at the social level becomes a cause of failure at the economic level. Therefore, political institutions fail to remedy the failure arising from the previous two levels, so that the possibilities of foreign powers interference in the state escalate.